2001
DOI: 10.1046/j.1365-2958.2001.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

The gametocyte‐activating factor xanthurenic acid stimulates an increase in membrane‐associated guanylyl cyclase activity in the human malaria parasite Plasmodium falciparum

Abstract: SummarySex is an obligate step in the life cycle of the malaria parasite and occurs in the midgut of the mosquito vector. With both Plasmodium falciparum and Plasmodium berghei, the tryptophan metabolite xanthurenic acid induces the release of motile male gametes from red blood cells (exflagellation), a prerequisite for fertilization. The addition of cGMP or phosphodiesterase inhibitors to cultures of mature gametocytes has also been shown to stimulate exflagellation. Here, we demonstrate that there is a guany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 33 publications
0
80
0
Order By: Relevance
“…XA, however, was shown to trigger guanylyl cyclase activity in gametocyte membranes (Muhia et al ., 2001). In P .…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…XA, however, was shown to trigger guanylyl cyclase activity in gametocyte membranes (Muhia et al ., 2001). In P .…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
“…Ca 2+ , on the other hand, was shown to inhibit guanylyl cyclase activity (Muhia et al ., 2001). In eukaryotic cells, the intracellular cGMP concentrations are generally regulated by cGMP‐synthetizing guanylyl cyclases and cGMP‐hydrolyzing phosphodiesterases (PDE).…”
Section: The Initiation Of Gametogenesismentioning
confidence: 99%
“…Once in the mosquito midgut, the intraerythrocytic gametocytes sense the change of hosts due to the perception of environmental factors present in the gut lumen, triggering their egress from the RBC and their transformation into gametes. Initially, a plasmodial guanylyl cyclase becomes activated, leading to the synthesis of cyclic GMP (cGMP) (Carucci et al, 2000;Muhia et al, 2001). The rise of cGMP activates the cGMP-dependent protein kinase G, which regulates the generation of PIP 2 (Alam et al, 2015;Brochet et al, 2014;McRobert et al, 2008).…”
Section: The Role Of Plasmodial Phospholipases During Life-cycle Progmentioning
confidence: 99%
“…For Plasmodium , an in vitro fertilization (IVF) assay has been established involving three factors required to induce gametogenesis: (1) a drop in temperature from 37 °C to 21 °C; (2) the presence of xanthurenic acid (XA), a previously determined mosquito-derived factor (Billker et al 1998 ); and (3) alkaline conditions (pH 8.0). Through IVF, it has been demonstrated that XA activates membrane-bound guanylate cyclase (GC) (Muhia et al 2001 ) and cGMP-dependent protein kinase (PKG) (McRobert et al 2008 ), which are essential for male exfl agellation. Moreover, N -methyl-hydroxylamine, an inhibitor of GC, inhibits exfl agellation (Kawamoto et al 1990 ).…”
Section: Sexual Differentiation and Gametogenesis Of Malaria Parasitesmentioning
confidence: 99%